CALPHAD modeling of metastable phases and ternary compounds in Ti-Al-N system. (December 2017) - Zhang, Yanhui; Franke, Peter; Seifert, Hans Jürgen
Abstract: The development and evaluation of thermodynamic databases for the Ti-Al-N system is important for a wide range of engineering alloys. In this work, we resorted to the integration of ab initio thermodynamics, experiments and CALPHAD modeling for a comprehensive understanding of the metastable and the ternary phases in Ti-Al-N system. The supersaturated solutions of (Ti, Al)N with both rocksalt and wurtzite structures were well described by using the sub-regular solution model. Thereby, the formation, the phase separation and the meta-solubility of TiAlN coatings were successfully elaborated by the metastable pseudo-binary TiN-AlN section and the PVD (physical vapor deposition) phase diagram. Moreover, a number of isothermal and isopleth sections were also calculated and compared with available experiments and previous thermodynamic assessments. For the first time the ternary compound of τ 3 was corrected as Ti 4 AlN 3 in our proposed database.